Diversified Polyketides With Anti-inflammatory Activities From Mangrove Endophytic Fungus Daldinia eschscholtzii KBJYZ-1 - Wang, Guisheng; Yin, Zhenhua; Wang, Senye; Yuan, Yilin; Chen, Yan; Kang, Wenyi (Frontiers in Microbiology, 2022)
Five new polyketide derivatives, eschscholin B (2), dalditone A-B (3-4), (1R, 4R)-5-methoxy-1,2,3,4-tetrahydronaphthalene-1,4-dio (5), and daldilene A (6), together with ten known metabolites (1, 7-15) were isolated from the mangrove endophytic fungi Daldinia eschscholtzii KBJYZ-1. Their structures and absolute configurations were established by extensive analysis of NMR and HRESIMS spectrum data combined with ECD calculations. Compounds 2 and 6 showed significant anti-inflammatory activities with IC50 values of 19.3 and 12.9 µM, respectively. Additionally, Western blot results suggested that compound 2 effectively inhibits the expression of iNOS and COX-2 in LPS-induced RAW264.7 cells. Further research of the underlying mechanism revealed that 2 exerts anti-inflammatory function by inactive MAPK and NF-κB signal pathways.